Tire force control for semi active magnetorheological damper suspension system using quarter heavy vehicle model - Sulaiman, Syabillah (2015)
This paper proposed semi active controller scheme for magnetorheological (MR) damper of a heavy vehicle suspension known as Tire Force Control (TFC). A reported algorithm in the literature to reduce tire force is Groundhook (GRD). Thus, the objective of this paper is to investigate the effectiveness of the proposed TFC algorithm compared to GRD. These algorithms are applied to a quarter heavy vehicle models, where the objective of the proposed controller is to reduce unsprung force (tire force). The simulation model was developed and simulated using MATLAB Simulink software. The use of semi active MR damper using TFC is analytically studied. Ride test was conducted at three different speeds and three bump heights, and the simulation results of TFC and GRD are compared and analysed. The results showed that the proposed controller is able to reduced tire force significantly compared to GRD control strategy.